Molecular cloning of lethal(2)giant larva, a recessive oncogene of Drosophila melanogaster. - Mechler, B.M.; McGinnis, W.; Gehring, W.J. (The EMBO Journal, 1985)
Recessive mutations at the lethal(2)giant larvae (l(2)gl) locus of Drosophila melanogaster cause a complex syndrome, which has as its most striking features the development of malignant neuroblastomas in the larval brain and tumors of the imaginal discs. A chromosomal segment containing the l(2)gl gene has been cloned. Within this segment a transcription unit has been localized which is structurally changed in all l(2)gl alleles examined. The developmental profile of expression of the two RNAs (6 and 4.5 kb) made by this transcription unit coincides with the two major terminal phases of cell proliferation in the developing fly, namely, early embryogenesis and late third instar larvae. Tumors are produced when both normal l(2)gl alleles are inactivated by deletion or insertional mutation. The normal function of the l(2)gl presumably controls the normal cell proliferation of the optic centers of the brain and the imaginal discs, as well as their post-mitotic differentiation.